PENANGANAN KELUHAN TAMU OLEH PRAMUSAJI DI BANQUET SECTION THE ZURI HOTELDUMAI - Juniarti Maula; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The development of the tourism industry in Indonesia has had a very good impact, namely in supporting state revenues. One form of the rapid development of tourism is the many tourist attractions and the construction of many star hotels. A hotel that is considered good is seen with good service too, because a service is also a benchmark for the size of complaints or guest complaints, especially the Banquet Section of The Zuri Hotel Dumai. The thing that must be done by the hotel The Zuri Hotel Dumai is to handle guest complaints. Handling guest complaints also requires several stages, including listening carefully, having empathy, apologizing and finally following up on problems and solving problems without harming anyone so that guests feel satisfied with their service. The purpose of this study was also to find out how to handle guest complaints, especially at the Banquet Section of The Zuri Hotel Dumai by using a qualitative descriptive research method to analyze problems based on the results of interviews, observation and documentation. This research was obtained from the results of interviews with the author to the HRD, Banquet Operational Manager, Banquet Service Supervisor. And the results of the research were carried out according to procedures, and the handling of guest complaints focused on the complaints given by these guests. Guest complaints occur at any time and require special attention from the Management of The Zuri Hotel Dumai. Keywords: The Handling of Guest Complaints